2011
DOI: 10.1007/s11250-011-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of detection procedures of Mycoplasma hyopneumoniae, Mycoplasma hyosynoviae, and Mycoplasma hyorhinis in lungs, tonsils, and synovial fluid of slaughtered pigs and their distributions in Thailand

Abstract: The aim of this study was to investigate whether direct PCR (DP) gave similar results to culture prior to PCR (CPP) for detecting mycoplasmas in different types of pig tissues. A total of 724 samples obtained from lungs, tonsils, or synovial fluids from 270 slaughtered pigs were used. The history of clinical signs, lung score, and the presence of joint lesions were recorded during sample collection. The rates of detection of Mycoplasma hyopneumoniae, Mycoplasma hyosynoviae, and Mycoplasma hyorhinis using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In this study, the use of nested-PCR in post-mortem samples showed high levels of M. hyopneumoniae detection, which reinforces its applicability to evaluate the etiological agent presence. Makhanon et al (2012) used pulmonary tissue from slaughter pigs as samples and found a 77.4% M. hyopneumoniae prevalence. According to the authors, this type of sample is the most reliable for the molecular diagnosis of slaughter pigs that are convalescent and pathogen carriers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the use of nested-PCR in post-mortem samples showed high levels of M. hyopneumoniae detection, which reinforces its applicability to evaluate the etiological agent presence. Makhanon et al (2012) used pulmonary tissue from slaughter pigs as samples and found a 77.4% M. hyopneumoniae prevalence. According to the authors, this type of sample is the most reliable for the molecular diagnosis of slaughter pigs that are convalescent and pathogen carriers.…”
Section: Resultsmentioning
confidence: 99%
“…A high prevalence of M. hyopneumoniae in swine herds has been reported, reaching 93.6% (Fablet et al, 2012;Makhanon et al, 2012). The presence of this microorganism in endemically infected areas might be influenced by management practices and the housing conditions of animals, considering that transmission through the airway frequently occurs between closed regions (Sibila et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Nathues et al [19] used a combination of PCR on nasal swabs and ELISA for antibodies in serum. Makhanon et al [24] compared the results of culture and PCR in various tissues of slaughtered pigs for the detection of different species of Mycoplasma. In the present study we used ELISA to detect antibodies in serum.…”
Section: Discussionmentioning
confidence: 99%
“…M. hyosynoviae and M. hyorhinis can be isolated from the tonsils and nasal cavity of experimentally inoculated and naturally exposed animals using standard culture procedures [ 9 15 16 24 ]. However, standard culture techniques are often complicated by overgrowth of other fast-growing bacteria [ 8 22 35 ].…”
Section: Discussionmentioning
confidence: 99%